Peroral endoscopic myotomy as a new approach in the treatment of patients with achalasia cardia - O.M. Kiosov; M.B. Danyliuk; M.A. Kubrak (Медицина неотложных состояний)
Background. Achalasia cardia is a disease characterized by an esophageal motility disorder in which the lower esophageal sphincter fails to fully relax in response to swallo-wing and esophageal motility progressively decreases. The aim of the work is to improve the outcomes of endoscopic treatment for esophageal achalasia by modifying peroral endoscopic myotomy (POEM) in stage II–III achalasia cardia. Materials and methods. In 2019–2023, 35 (100.0 %) patients with stage II–III achalasia cardia were examined and underwent POEM at the multidisciplinary surgical department in the Educational and Scientific Medical Center “University Clinic” of the Zaporizhzhia State Medical and Pharmaceutical University. The diagnosis was made based on the following data: complaints, clinical course, esophagram, endoscopic diagnosis, and computed tomography. The average age of the patients was 50.0 ± 15.7 years. Analyzing the frequency of this disease according to the WHO age classification, there were 16 (45.7 %) young, 8 (22.9 %) middle-aged, 10 (28.6 %) elderly, and 1 (2.8 %) senile patient. The group was equal in terms of gender: 16 men (45.7 %) and 19 women (54.3 %), p = 0.9654. Inclusion criteria: age over 18 years, stage II–III achalasia cardia, informed consent of a patient. Exclusion criteria: achalasia cardia stage I, as we believe that at this stage only conservative treatment and balloon dilatation are indicated; achalasia cardia stage IV for which only Heller myotomy with Dor fundoplication are indicated. Results. All patients of the study group were operated by the method of POEM under total intravenous ane-sthesia with artificial lung ventilation. Esophageal myotomy was performed along the posterior wall, considering the risk of recurrence and preservation of the anterior wall for repeated peroral myotomy or laparoscopic Heller myotomy. The length of the myotomy was determined depending on the stage of achalasia. So, for stage II, the beginning of the endoscopic tunnel formation and myotomy was determined from the first persistent esophageal spasm, which most often corresponded to a distance of 25.0 ± 2.0 cm from the incisors and, accordingly, myotomy of the esophagus, lower esophageal sphincter, and gastric myotomy averaged 15.0 ± 3.0 cm. We noted that in all operated patients six months after the operation, a propulsive activity appeared during contrast X-ray of the esophagus, and its volume decreased from 5.6 ± 0.4 cm at stage II to 2.3–4.1 cm (p = 0.0324) and from 7.4 ± 0.2 cm at stage III to 3.6 ± 0.8 cm (p = 0.0267), which indicates a decreased pressure in the lower esophageal sphincter after surgery. Based on the evaluation of the results of multichannel esophageal gastric pH monitoring, reflux was confirmed in 1 (6.7 %) patient with achalasia stage II and in 1 (5.0 %) case with achalasia stage III. Conclusions. Peroral endoscopic myotomy is an effective minimally invasive method of treating patients with achalasia cardia stage II–III. According to the Eckardt symptom score, reliable results were achieved already one month after surgery: 7.6 ± 1.1 points before surgery and 2.1 ± 0.4 points when evaluated one month after surgical treatment (p < 0.0001, U = 475.0). Given the effectiveness and minimal trauma, the low risk of postoperative complications, a significant reduction in hospital stay and rapid postoperative rehabilitation, POEM can be an alternative to laparoscopic Heller myotomy.